Evaluation of ammonia fueled engine for a bulk carrier in marine decarbonization pathways. (15th December 2022) - Ejder, Emir; Arslanoğlu, Yasin
Abstract: This study highlights that in addition to using ammonia in the maritime sector and integrating it into the ship concept, it is a challenging option for shipowners in terms of capital and operational expenditures. In this study, the typical marine-type fuels used in the main engines of a bulk carrier were compared to ammonia in a Techno-Economic Analysis. The bulk carrier features a conventional main engine system, and operational data was acquired to determine how much ammonia was consumed. The ship is classified using the Energy Efficiency Existing Ship Index (EEXI) and the Carbon Intensity Indicator (CII). To determine its economic viability, Monte-Carlo Simulation is utilized. In addition, a cost scenario for in-service bulk carriers was developed, with an emphasis on their application. Ammonia is used to minimize petroleum consumption, but it is not cost-effective for long-term financial sustainability, and the installation cost is more than 5 million USD. MAC calculation was made according to NPV values and CO2 reduction results and 3816.42 $/tCO2 e was obtained. According to the article, ammonia is more suitable for newly built marine vessels. With the study, a method that can be used in the feasibility studies of different alternative technologies for the existing ships of the shipping companies is presented in the literature.